Novel Fe-N/C Type Catalysts Based on Carbide Derived Carbon for Oxygen Reduction Reaction. (19th June 2018) - Jäger, Rutha; Kasatkin, Piia Ereth; Teppor, Patrick; Härk, Eneli; Joost, Urmas; Romann, Tavo; Tallo, Indrek; Kanarbik, Rait; Paiste, Päärn; Kirsimäe, Kalle; Lust, Enn
Abstract : Novel Fe-N/C type catalysts for the oxygen reduction reaction (ORR) were synthesized using FeSO4 ∙7H2 O as the Fe precursor, 2, 2'-bipyridine as N precursor and carbide (TiC, Mo2 C or SiC) derived carbons as the carbon supports. ORR activity studied by using the rotating disk electrode method increases in the following order: C(SiC) < C(TiC) < C(Mo2 C) < Fe-N/C(TiC) < Fe-N/C(Mo2 C) < Fe-N/C(SiC). The 140-hour durability tests demonstrated that different Fe-N/C catalysts stability noticeably depends on the structure of the carbon support used. The degradation rate for Fe-N/C(Mo2 C) and for Fe-N/C(SiC) is 0.9 mV h -1, but significantly smaller value (0.3 mV h -1 ) has been established for Fe-N/C(TiC) catalyst. Fe-N/C(SiC) showed the highest ORR activity, but the Fe-N/C(TiC) catalyst was the most stable in 0.1M HClO4 electrolyte solution.